DEVELOPING AND STANDARDIZING THE TEST OF PEDAGOGICAL AND PROFESSIONALISM COMPETENCE FOR PHYSICAL EDUCATION TEACHERS IN ELEMENTARY SCHOOLS - Masrun Masrun; Hariadi Hariadi; Arie Asnaldi (Journal Physical Education, Health and Recreation, 2022)
The main objective of this study is to develop and standardize an instrument of pedagogical and professional competency for Physical Education teachers at elementary school level. Based on Law No. 14 of 2002, teachers in Indonesia are required to master four competencies, namely: pedagogy, professional, personality and social. Currently, there are only few numbers of standardized instruments to test these four competencies. Thus, this study aims at developing and standardizing a pedagogical and professional competency instrument in a form of a test. This study applied a procedural research and development (RnD) model using the following steps: research and collection preliminary, research planning, early product development, expert validation, product revision, early test, product revision, field test, final product revision and mass product manufacture. The test subjects in this study were physical education teachers at the elementary school level. Based on data from Education Authorites in Padang, the total population in this study was 480 people and the sample was taken purposively. During the early test, it was carried out to 20 samples and during the field test, it was carried out on 20% of the total population, namely 84 people. Standardization of the instrument was carried out by conducting several analysis, namely: validity, reliability, item difficulty level, item discriminating power, practicality test, and effectiveness. Data were processed using IBM SPSS statistical program with p < 0.05. Based on the results of processing and processing, a standardized instrument that can measure pedagogical and professional competence for Physical Education teachers was successfully made.